A cell wall-localized glycine-rich protein of dodder acts as pathogen-associated molecular pattern - Slaby, Peter; Körner, Max; Albert, Markus (Communitative and Integrative Biology, 2021)
Cuscuta reflexa (giant dodder) is an obligate stem holoparasite withdrawing water, nutrients, and carbohydrates from its hosts. For a broad spectrum of host plants, C. reflexa usually stays unrecognized. The cultivated tomato Solanum lycopersicum, as one notable exception, possesses a leucine-rich repeat receptor protein (LRR-RP), Cuscuta receptor 1 (CuRe1), which enables tomato to recognize C. reflexa as a dangerous parasitic invader and to respond with plant immune responses. During the infection process, a glycine-rich protein (GRP) is freed from C. reflexa and gets detected by CuRe1. Here, we focus on the subcellular localization of the GRP within plant cell walls using a fluorescence based co-localization.
Created from Fastlane, Scopus look-up
Keywords: CuRe1; Cuscuta reflexa; Glycine-rich protein; GRP; parasitic plants

An RLP23-SOBIR1-BAK1 complex mediates NLP-triggered immunity - Albert, Isabell; Boehm, Hannah; Albert, Markus; Feiler, Christina E.; Imkampe, Julia; Wallmeroth, Niklas; Brancato, Caterina; Raaymakers, Tom M.; Oome, Stan; Zhang, Heqiao; Krol, Elzbieta; Grefen, Christopher; et al. (Nature Plants, 2015)
Plants and animals employ innate immune systems to cope with microbial infection. Pattern-triggered immunity relies on the recognition of microbe-derived patterns by pattern recognition receptors (PRRs). Necrosis and ethylene-inducing peptide 1-like proteins (NLPs) constitute plant immunogenic patterns that are unique, as these proteins are produced by multiple prokaryotic (bacterial) and eukaryotic (fungal, oomycete) species. Here we show that the leucine-rich repeat receptor protein (LRR-RP) RLP23 binds in vivo to a conserved 20-amino-acid fragment found in most NLPs (nlp20), thereby mediating immune activation in Arabidopsis thaliana. RLP23 forms a constitutive, ligand-independent complex with the LRR receptor kinase (LRR-RK) SOBIR1 (Suppressor of Brassinosteroid insensitive 1 (BRI1)-associated kinase (BAK1)-interacting receptor kinase 1), and recruits a second LRR-RK, BAK1, into a tripartite complex upon ligand binding. Stable, ectopic expression of RLP23 in potato (Solanum tuberosum) confers nlp20 pattern recognition and enhanced immunity to destructive oomycete and fungal plant pathogens, such as Phytophthora infestans and Sclerotinia sclerotiorum. PRRs that recognize widespread microbial patterns might be particularly suited for engineering immunity in crop plants.
CRIS-Team Scopus Importer:2020-03-09

Arabidopsis thaliana pattern recognition receptors for bacterial elongation factor tu and flagellin can be combined to form functional chimeric receptors - Albert, Markus; Jehle, Anna K.; Mueller, Katharina; Eisele, Claudia; Lipschis, Martin; Felix, Georg (Journal of Biological Chemistry, 2010)
The receptor kinase EFR of Arabidopsis thaliana detects the microbe-associated molecular pattern elf18, a peptide that represents the N terminus of bacterial elongation factor Tu. Here, we tested subdomains of EFR for their importance in receptor function. Transient expression of tagged versions of EFR and EFR lacking its cytoplasmic domain in leaves of Nicotiana benthamiana resulted in functional binding sites for elf18. No binding of ligand was found with the ectodomain lacking the transmembrane domain or with EFR lacking the first 5 of its 21 leucine-rich repeats (LRRs). EFR is structurally related to the receptor kinase flagellin-sensing 2 (FLS2) that detects bacterial flagellin. Chimeric receptors with subdomains of FLS2 substituting for corresponding parts of EFR were tested for functionality in ligand binding and receptor activation assays. Substituting the transmembrane domain and the cytoplasmic domain resulted in a fully functional receptor for elf18. Replacing also the outer juxtamembrane domain with that of FLS2 led to a receptor with full affinity for elf18 but with a lower efficiency in response activation. Extending the substitution to encompass also the last two of the LRRs abolished binding and receptor activation. Substitution of the N terminus by the first six LRRs from FLS2 reduced binding affinity and strongly affected receptor activation. In summary, chimeric receptors allow mapping of subdomains relevant for ligand binding and receptor activation. The results also show that modular assembly of chimeras from different receptors can be used to form functional receptors. © 2010 by The American Society for Biochemistry and Molecular Biology, Inc.
CRIS-Team Scopus Importer:2020-03-09

A two-hybrid-receptor assay demonstrates heteromer formation as switch-on for plant immune receptors - Albert, Markus; Jehle, Anna Kristina; Fuerst, Ursula; Chinchilla, Delphine; Boller, Thomas; Felix, Georg (Plant Physiology, 2013)
Receptor kinases sense extracellular signals and trigger intracellular signaling and physiological responses. However, how does signal binding to the extracellular domain activate the cytoplasmic kinase domain? Activation of the plant immunoreceptor Flagellin sensing2 (FLS2) by its bacterial ligand flagellin or the peptide-epitope flg22 coincides with rapid complex formation with a second receptor kinase termed brassinosteroid receptor1 associated kinase1 (BAK1). Here, we show that the receptor pair of FLS2 and BAK1 is also functional when the roles of the complex partners are reversed by swapping their cytosolic domains. This reciprocal constellation prevents interference by redundant partners that can partially substitute for BAK1 and demonstrates that formation of the heteromeric complex is the molecular switch for transmembrane signaling. A similar approach with swaps between the Elongation factor-Tu receptor and BAK1 also resulted in a functional receptor/coreceptor pair, suggesting that a "two-hybrid-receptor assay" is of more general use for studying heteromeric receptor complexes. © 2013 American Society of Plant Biologists. All Rights Reserved.
CRIS-Team Scopus Importer:2020-03-09

Calcium signaling during the plant-plant interaction of parasitic Cuscuta reflexa with its hosts - Albert, Markus; Kaiser, Bettina; van der Krol, Sander; Kaldenhoff, Ralf (Plant Signaling & Behavior, 2010)
The plant parasite Cuscuta reflexa induces various responses in compatible and incompatible host plants. The visual reactions of both types of host plants including obvious morphological changes require the recognition of Cuscuta ssp. A consequently initiated signaling cascade is triggered which leads to a tolerance of the infection or, in the case of some incompatible host plants, to resistance. Calcium (Ca 2+) release is the major second messenger during signal transduction. Therefore, we have studied Ca 2+ spiking in tomato and tobacco during infection with C. reflexa. In our recently published study1 Ca 2+ signals were monitored as bioluminescence in aequorin-expressing tomato plants after the onset of C. reflexa infestation. Signals at the attachment sites were observed from 30 to 48 h after infection. In an assay with leaf disks of aequorin-expressing tomato which were treated with different C. reflexa plant extracts it turned out that the substance that induced Ca 2+ release in the host plant was closely linked to the parasite's haustoria. © 2010 Landes Bioscience.
CRIS-Team Scopus Importer:2020-03-09
Keywords: Calcium signaling; Cuscuta; Dodder; Plant parasitism

Chemiluminescence-based detection of peptide activity and peptide-receptor binding in plants - Wildhagen, Mari; Albert, Markus; Butenko, Melinka A. (Plant Genomics, 2017)
In living organisms, physical interaction of ligand molecules with their cognate receptors is an indispensable requirement for the initiation of cellular signaling pathways. To technically prove the biochemical interaction of ligands with their corresponding receptor, a biologically active but labeled peptide is required. Easily scorable bioassays, such as the production of reactive oxygen species, can be used to quantify the activity of a peptide. By using chemiluminescent probes, such as acridinium esters, as conjugates to label peptide ligands of interest, quantitative measurements of ligand-receptor binding can be performed in standard luminometers. Here we describe how this binding approach can be used to reveal peptide ligand-receptor binding in plant material.
CRIS-Team Scopus Importer:2020-03-09
Keywords: Acridinium ester label; Chemiluminescence detection; Ligand-receptor binding; Oxidative burst

Chimeric FLS2 receptors reveal the basis for differential flagellin perception in arabidopsis and tomato - Mueller, Katharina; Bittel, Pascal; Chinchilla, Delphine; Jehle, Anna K.; Albert, Markus; Boller, Thomas; Felix, Georg (The Plant Cell, 2012)
The flagellin receptor of Arabidopsis thaliana, At-FLAGELLIN SENSING2 (FLS2), has become a model for mechanistic and functional studies on plant immune receptors. Here, we started out with a comparison of At-FLS2 and the orthologous tomato (Solanum lycopersicum) receptor Sl-FLS2. Both receptors specifically responded to picomolar concentrations of the genuine flg22 ligand but proved insensitive to >106-fold higher concentrations of CLV3 peptides that have recently been reported as a second type of ligand for At-FLS2. At-FLS2 and Sl-FLS2 exhibit species-specific differences in the recognition of shortened or sequence-modified flg22 ligands. To map the sites responsible for these species-specific traits on the FLS2 receptors, we performed domain swaps, substituting subsets of the 28 leucine-rich repeats (LRRs) in At-FLS2 with the corresponding LRRs from Sl-FLS2. We found that the LRRs 7 to 10 of Sl-FLS2 determine the high affinity of Sl-FLS2 for the core part RINSAKDD of flg22. In addition, we discovered importance of the LRRs 19 to 24 for the responsiveness to C-terminally modified flagellin peptides. These results indicate that ligand perception in FLS2 is a complex molecular process that involves LRRs from both the outermost and innermost LRRs of the FLS2 ectodomain. © 2012 American Society of Plant Biologists. All rights reserved.
CRIS-Team Scopus Importer:2020-03-09

Chimeric receptors of the Arabidopsis thaliana pattern recognition receptors EFR and FLS2 - Albert, Markus; Felix, Georg (Plant Signaling & Behavior, 2010)
FLS2 and EFR are pattern recognition receptors in Arabidopsis thaliana perceiving the bacterial proteins flagellin and Elongation factor Tu (EF-Tu). Both receptors belong to the >200 membered protein family of Leucine-Rich Repeat Receptor Kinases (LRR-RKs) in Arabidopsis. FLS2 and EFR are engaged in the activation of a common intracellular signal output and they belong to the same subfamily of LRR-RKs, sharing structural features like the intracellular kinase domain and the ectodomain organized in LRRs. On the amino acid sequence level, however, they are only <50% identical even in their kinase domains. In our recently published paper1 we demonstrated that it is possible to create chimeric receptors of EFR and FLS2 which are fully functional in ligand binding and receptor activation. Chimeric receptors consisting of the complete EFR ectodomain and the FLS2 kinase domain proved to be sensitive to elf18, the minimal peptide required for EF-Tu recognition, similar to the native EFR. In chimeric receptors where parts of the FLS2 ectodomain were swapped into the EFR LRR-domain, the receptor function was strongly affected even in cases with only small fragments exchanged. In this addendum we want to address problems and limits but also possibilities and chances of studying receptor functions using a chimeric approach. © 2010 Landes Bioscience.
CRIS-Team Scopus Importer:2020-03-09
Keywords: Chimeric receptors; EFR; Flagellin perception; FLS2; MAMP; Pattern recognition receptors

Complex N-Glycans Are Important for Normal Fruit Ripening and Seed Development in Tomato - Kaulfuerst-Soboll, Heidi; Mertens-Beer, Melanie; Brehler, Randolf; Albert, Markus; Von Schaewen, Antje (Frontiers in Plant Science, 2021)
Complex N-glycan modification of secretory glycoproteins in plants is still not well understood. Essential in animals, where a lack of complex N-glycans is embryo-lethal, their presence in plants seemed less relevant for a long time mostly because Arabidopsis thaliana cgl1 mutants lacking N-acetyl-glucosaminyltransferase I (GNTI, the enzyme initiating complex N-glycan maturation in the Golgi apparatus) are viable and showed only minor impairments regarding stress tolerance or development. A different picture emerged when a rice (Oryza sativa) gntI T-DNA mutant was found to be unable to reach the reproductive stage. Here, we report on tomato (Solanum lycopersicum) lines that showed severe impairments upon two RNA interference (RNAi) approaches. Originally created to shed light on the role of core α1,3-fucose and β1,2-xylose residues in food allergy, plants with strongly reduced GNTI activity developed necrotic fruit-attached stalks and early fruit drop combined with patchy incomplete ripening. Correspondingly, semiquantitative RT-PCR of the abscission zone (az) revealed an increase of abscission markers. Also, GNTI-RNA interference (RNAi) plants were more susceptible to sporadic infection. To obtain vital tomatoes with comparable low allergenic potential, Golgi α-mannosidase II (MANII) was chosen as the second target. The resulting phenotypes were oppositional: MANII-reduced plants carried normal-looking fruits that remained attached for extended time without signs of necrosis. Fruits contained no or only few, but enlarged, seeds. Furthermore, leaves developed rolled-up rims simultaneously during the reproductive stage. Trials to cross MANII-reduced plants failed, while GNTI-reduced plants could be (back-)crossed, retaining their characteristic phenotype. This phenotype could not be overcome by ethephon or indole-3-acetic acid (IAA) application, but the latter was able to mimic patchy fruit ripening in wild-type. Phytohormones measured in leaves and 1-aminocyclopropane-1-carboxylic acid (ACC) contents in fruits showed no significant differences. Together, the findings hint at altered liberation/perception of protein-bound N-glycans, known to trigger auxin-like effects. Concomitantly, semiquantitative RT-PCR analysis revealed differences in auxin-responsive genes, indicating the importance of complex N-glycan modification for hormone signaling/crosstalk. Another possible role of altered glycoprotein life span seems subordinate, as concluded from transient expression of Arabidopsis KORRIGAN KOR1-GFP fusion proteins in RNAi plants of Nicotiana benthamiana. In summary, our analyses stress the importance of complex N-glycan maturation for normal plant responses, especially in fruit-bearing crops like tomato.
CRIS-Team Scopus Importer:2021-04-02
Keywords: auxin-like effects; complex N-glycans; free N-glycans; fruit abscission; fruit ripening; GNTI; hormone signaling; MANII

Contamination risks in work with synthetic peptides: Flg22 as an example of a pirate in commercial peptide preparations - Mueller, Katharina; Chinchilla, Delphine; Albert, Markus; Jehle, Anna K.; Kalbacher, Hubert; Boller, Thomas; Felix, Georg (The Plant Cell, 2012)
The pattern recognition receptor FLAGELLIN SENSING2 (FLS2) renders plant cells responsive to subnanomolar concentrations of flg22, the active epitope of bacterial flagellin. We recently observed that a preparation of the peptide IDL1, a signal known to regulate abscission processes via the receptor kinases HAESA and HAESA-like2, apparently triggered Arabidopsis thaliana cells in an FLS2-dependent manner. However, closer investigation revealed that this activity was due to contamination by a flg22-type peptide, and newly synthesized IDL1 peptide was completely inactive in FLS2 signaling. This raised alert over contamination events occurring in the process of synthesis or handling of peptides. Two recent reports have suggested that FLS2 has further specificities for structurally unrelated peptides derived from CLV3 and from Ax21. We thus scrutinized these peptides for activity in Arabidopsis cells as well. While responding to <1 nM flg22, Arabidopsis cells proved blind even to 100 μM concentrations of CLV3p and axYs22. Our results confirm the exquisite sensitivity and selectivity of FLS2 for flg22. They also show that inadvertent contaminations with flg22-type peptides do occur and can be detected even in trace amounts by FLS2. © 2012 American Society of Plant Biologists. All rights reserved.
CRIS-Team Scopus Importer:2020-03-09

Cuscuta reflexa invasion induces Ca2+ release in its host - Albert, Markus; Van Der Krol, S.; Kaldenhoff, R. (Plant Biology, 2010)
Cuscuta reflexa induces a variety of reaction in its hosts. Some of these are visual reactions, and it is clear that these morphological changes are preceded by events at the molecular level, where signal transduction is one of the early processes. Calcium (Ca2+) release is the major second messenger during signal transduction, and we therefore studied Ca2+ spiking in tomato during infection with C. reflexa. Bioluminescence in aequorin-expressing tomato was monitored for 48 h after the onset of Cuscuta infestation. Signals at the attachment sites were observed from 30 to 48 h. Treatment of aequorin-expressing tomato leaf disks with Cuscuta plant extracts suggested that the substance that induced Ca2+ release from the host was closely linked to parasite haustoria. © 2010 German Botanical Society and The Royal Botanical Society of the Netherlands.
CRIS-Team Scopus Importer:2020-03-09
Keywords: Aequorin; Cuscuta reflexa; Parasitic plants; Tomato

Detection of the plant parasite Cuscuta reflexa by a tomato cell surface receptor - Hegenauer, Volker; Fuerst, Ursula; Kaiser, Bettina; Smoker, Matthew; Zipfel, Cyril; Felix, Georg; Stahl, Mark; Albert, Markus (Science, 2016)
Parasitic plants are a constraint on agricultureworldwide. Cuscuta reflexa is a stem holoparasite that infests most dicotyledonous plants. One exception is tomato, which is resistant to C. reflexa.We discovered that tomato responds to a small peptide factor occurring in Cuscuta spp. with immune responses typically activated after perception of microbe-associated molecular patterns.We identified the cell surface receptor-like protein CUSCUTA RECEPTOR 1 (CuRe1) as essential for the perception of this parasite-associated molecular pattern. CuRe1 is sufficient to confer responsiveness to the Cuscuta factor and increased resistance to parasitic C. reflexa when heterologously expressed in otherwise susceptible host plants. Our findings reveal that plants recognize parasitic plants in a manner similar to perception of microbial pathogens.
CRIS-Team Scopus Importer:2020-03-09

Distinct immune sensor systems for fungal endopolygalacturonases in closely related Brassicaceae - Zhang, Lisha; Hua, Chenlei; Pruitt, Rory N.; Qin, Si; Wang, Lei; Albert, Isabell; Albert, Markus; Van Kan, Jan A. L.; Nuernberger, Thorsten (Nature Plants, 2021)
Plant pattern recognition receptors (PRRs) facilitate recognition of microbial patterns and mediate activation of plant immunity. Arabidopsis thaliana RLP42 senses fungal endopolygalacturonases (PGs) and triggers plant defence through complex formation with SOBIR1 and SERK co-receptors. Here, we show that a conserved 9-amino-acid fragment pg9(At) within PGs is sufficient to activate RLP42-dependent plant immunity. Structure–function analysis reveals essential roles of amino acid residues within the RLP42 leucine-rich repeat and island domains for ligand binding and PRR complex assembly. Sensitivity to pg9(At), which is restricted to A. thaliana and exhibits scattered accession specificity, is unusual for known PRRs. Arabidopsis arenosa and Brassica rapa, two Brassicaceae species closely related to A. thaliana, respectively perceive immunogenic PG fragments pg20(Aa) and pg36(Bra), which are structurally distinct from pg9(At). Our study provides evidence for rapid evolution of polymorphic PG sensors with distinct pattern specificities within a single plant family.
CRIS-Team Scopus Importer:2021-08-13

Engineered Agrobacterium improves transformation by mitigating plant immunity detection - Yang, Fan; Li, Guangyong; Felix, Georg; Albert, Markus; Guo, Ming (New Phytologist, 2023)
center dot Agrobacterium tumefaciens microbe-associated molecular pattern elongation factor Tu (EF-Tu) is perceived by orthologs of the Arabidopsis immune receptor EFR activating pattern-triggered immunity (PTI) that causes reduced T-DNA-mediated transient expression. We altered EF-Tu in A. tumefaciens to reduce PTI and improved transformation efficiency.center dot A robust computational pipeline was established to detect EF-Tu protein variation in a large set of plant bacterial species and identified EF-Tu variants from bacterial pathogen Pseudomonas syringae pv. tomato DC3000 that allow the pathogen to escape EFR perception. Agrobacterium tumefaciens strains were engineered to substitute EF-Tu with DC3000 variants and examined their transformation efficiency in plants.center dot Elongation factor Tu variants with rarely occurred amino acid residues were identified within DC3000 EF-Tu that mitigates recognition by EFR. Agrobacterium tumefaciens strains were engineered by expressing DC3000 EF-Tu instead of native agrobacterial EF-Tu and resulted in decreased plant immunity detection.center dot These engineered A. tumefaciens strains displayed an increased efficiency in transient expression in both Arabidopsis thaliana and Camelina sativa. The results support the potential application of these strains as improved vehicles to introduce transgenic alleles into members of the Brassicaceae family.
CRIS-Team WoS Importer:2023-02-17

In-vivo Cross-linking of Biotinylated Peptide Ligands to Cell Surface Receptors - Burggraf, Ronja; Albert, Markus (Methods in Molecular Biology, 2024)
In-vivo cross-linking of biotinylated peptides is a technique to analyze the interaction of small proteins or peptide ligands with their corresponding receptors. Here, we describe an in-vivo method in which leaves of living plants, transiently expressing receptor proteins, are infiltrated with biotinylated peptides. The interaction between ligand and receptor is irreversibly fixed by the infiltration of a cross-linking agent. Subsequently, co-immunoprecipitation is used to pull down the receptor-ligand pair. After western blotting, the biotin tag of the ligand peptide cross-linked to the receptor can be detected by streptavidin-AP conjugate on the membrane.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Biotinylated peptides; Co-immunoprecipitation (Co-IP); In-vivo cross-linking; Peptide-receptor interaction; Protein expression in plants; SDS-polyacrylamide gel electrophoresis (SDS-PAGE); Western blot

Mechanisms of resistance and virulence in parasitic plant-host interactions - Albert, Markus; Axtell, Michael J.; Timko, Michael P. (Plant Physiology, 2021)
Parasitic plants pose a major biotic threat to plant growth and development and lead to losses in crop productivity of billions of USD annually. By comparison with "normal"autotrophic plants, parasitic plants live a heterotrophic lifestyle and rely on water, solutes and to a greater (holoparasitic plants) or lesser extent (hemiparasitic plants) on sugars from other host plants. Most hosts are unable to detect an infestation by plant parasites or unable to fend off these parasitic invaders. However, a few hosts have evolved defense strategies to avoid infestation or protect themselves actively post-attack often leading to full or partial resistance. Here, we review the current state of our understanding of the defense strategies to plant parasitism used by host plants with emphasis on the active molecular resistance mechanisms. Furthermore, we outline the perspectives and the potential of future studies that will be indispensable to develop and breed resistant crops.
CRIS-Team Scopus Importer:2021-05-21

Parasitic Cuscuta factor(s) and the detection by tomato initiates plant defense - Fürst, Ursula; Hegenauer, Volker; Kaiser, Bettina; Körner, Max; Welz, Max; Albert, Markus (Communitative and Integrative Biology, 2016)
Dodders (Cuscuta spp.) are holoparasitic plants that enwind stems of host plants and penetrate those by haustoria to connect to the vascular bundles. Having a broad host plant spectrum, Cuscuta spp infect nearly all dicot plants - only cultivated tomato as one exception is mounting an active defense specifically against C. reflexa. In a recent work we identified a pattern recognition receptor of tomato, "Cuscuta Receptor 1" (CuRe1), which is critical to detect a "Cuscuta factor" (CuF) and initiate defense responses such as the production of ethylene or the generation of reactive oxygen species. CuRe1 also contributes to the tomato resistance against C. reflexa. Here we point to the fact that CuRe1 is not the only relevant component for full tomato resistance but it requires additional defense mechanisms, or receptors, respectively, to totally fend off the parasite.
CRIS-Team Scopus Importer:2020-03-09
Keywords: Cuscuta; Cuscuta factor; Parasitic plant; Pattern recognition receptor; Plant immunity; Plant-plant interaction

Parasitic plants of the genus Cuscuta and their interaction with susceptible and resistant host plants - Kaiser, Bettina; Vogg, Gerd; Fuerst, Ursula B.; Albert, Markus (Frontiers in Plant Science, 2015)
By comparison with plant–microbe interaction, little is known about the interaction of parasitic plants with their hosts. Plants of the genus Cuscuta belong to the family of Cuscutaceae and comprise about 200 species, all of which live as stem holoparasites on other plants. Cuscuta spp. possess no roots nor fully expanded leaves and the vegetative portion appears to be a stem only. The parasite winds around plants and penetrates the host stems via haustoria, forming direct connections to the vascular bundles of their hosts to withdraw water, carbohydrates, and other solutes. Besides susceptible hosts, a few plants exist that exhibit an active resistance against infestation by Cuscuta spp. For example, cultivated tomato (Solanum lycopersicum) fends off Cuscuta reflexa by means of a hypersensitive-type response occurring in the early penetration phase. This report on the plant–plant dialog between Cuscuta spp. and its host plants focuses on the incompatible interaction of C. reflexa with tomato.
CRIS-Team Scopus Importer:2020-03-09
Keywords: Cuscuta; Dodder; Parasitic plants; Plant immunity; Plant–plant interaction; Resistance; Symbiosis

Peptides as triggers of plant defence - Albert, Markus (Journal of Experimental Botany, 2013)
Plants are confronted with several biotic stresses such as microbial pathogens and other herbivores. To defend against such attackers, plants possess an array of pattern recognition receptors (PRRs) that sense the danger and consequently initiate a defence programme that prevents further damage and spreading of the pest. Characteristic pathogenic structures, so-called microbe-associated molecular patterns (MAMPs), serve as signals that allow the plant to sense invaders. Additionally, pathogens wound or damage the plant and the resulting release of damageassociated molecular patterns (DAMPs) serves as a warning signal. This review focuses on peptides that serve as triggers or amplifiers of plant defence and thus follow the definition of a MAMP or a DAMP. © The Author 2013. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved.
CRIS-Team Scopus Importer:2020-03-09
Keywords: Damage-associated molecular pattern; Ligand-receptor interaction; Microbe-associated molecular pattern; Pattern recognition receptors; Peptide ligand; Plant defence; Plant immunity

Perception of Agrobacterium tumefaciens flagellin by FLS2XL confers resistance to crown gall disease - Fuerst, Ursula; Zeng, Yi; Albert, Markus; Witte, Anna Kristina; Fliegmann, Judith; Felix, Georg (Nature Plants, 2020)
Bacterial flagella are perceived by the innate immune systems of plants1 and animals2 alike, triggering resistance. Common to higher plants is the immunoreceptor FLAGELLIN-SENSING 2 (FLS2)3, which detects flagellin via its most conserved epitope, flg22. Agrobacterium tumefaciens, which causes crown gall disease in many crop plants, has a highly diverged flg22 epitope and evades immunodetection by plants so far studied. We asked whether, as a next step in this game of ‘hide and seek’, there are plant species that have evolved immunoreceptors with specificity for the camouflaged flg22Atum of A. tumefaciens. In the wild grape species Vitis riparia, we discovered FLS2XL, a previously unknown form of FLS2, that provides exquisite sensitivity to typical flg22 and to flg22Atum. As exemplified by ectopic expression in tobacco, FLS2XL can limit crown gall disease caused by A. tumefaciens.
CRIS-Team Scopus Importer:2020-03-09

Perception of the novel MAMP eMax from different Xanthomonas species requires the Arabidopsis receptor-like protein remax and the receptor kinase SOBIR - Jehle, Anna Kristina; Fürst, Ursula; Lipschis, Martin; Albert, Markus; Felix, Georg (Plant Signaling & Behavior, 2013)
As part of their innate immune system plants carry a number of pattern recognition receptors (PRR s) that can detect a broad range of microbe-associated molecular patterns (MAM Ps). In a recently published article1 we described a novel, proteinaceous MAM P termed eMax (enigmatic MAM P of Xanthomonas) that derives from Xanthomonas and gets recognized by the receptor-like protein ReMA X (RECEPTOR OF eMax) of Arabidopsis thaliana. ReMA X has no ortholog in Nicotiana benthamiana and this species does not respond to eMax even when transformed with ReMA X. However, interfamily transfer of eMax perception was successful with a chimeric form of ReMA X where the C-terminal part of the protein was replaced by the corresponding part of the tomato RLP EIX2 (ETH YLENE IN DUCIN G XYLANA SE2). In this addendum we describe the difficulties with the purification and identification of the MAM P eMax and we present data demonstrating that functionality of ReMA X, much like that of related RLPs, depends on the presence of the receptor kinase SOBIR (SUPPRESSOR OF BIR 1-1). © 2013 Landes Bioscience.
CRIS-Team Scopus Importer:2020-03-09
Keywords: Arabidopsis thaliana; Microbe-associated molecular pattern; Pattern recognition receptor; Plant innate immunity; Xanthomonas

Plants under stress by parasitic plants - Hegenauer, Volker; Koerner, Max; Albert, Markus (Current Opinion in Plant Biology, 2017)
In addition to other biotic stresses, parasitic plants pose an additional threat to plants and cause crop losses, worldwide. Plant parasites directly connect to the vasculature of host plants thereby stealing water, nutrients, and carbohydrates consequently leading to tremendously reduced biomass and losses in seed yields of the infected host plants. Initial steps to understand the molecular resistance mechanisms and the successes in ancient and recent breeding efforts will provide fundamental knowledge to further generate crop plants that will resist attacks by plant parasites.
CRIS-Team Scopus Importer:2020-03-09

Quantitative detection of oxidative burst upon activation of plant receptor kinases - Albert, Markus; Fürst, Ursula (Plant Receptor Kinases, 2017)
The oxidative burst or the production of reactive oxygen species (ROS) is a typical cellular response of both plants and animals to diverse abiotic and biotic stresses. Mainly, the (re-)active oxygen species include the superoxide anion (O2−), hydrogen peroxide (H2O2), and the hydroxyl radical (OH•). Here, we outline the detection of extracellularly produced ROS in plant leaf pieces using a chemiluminescence-based bioassay with the luminol L-012 as a substrate being oxidized in the presence of ROS. Since this type of assay is in use in many laboratories, e.g., as a readout for activation of plant receptor kinases, we include a discussion on the interpretation of results and points addressing problems with the buffers at suboptimal pH values that negatively influence the chemiluminescence production.
CRIS-Team Scopus Importer:2020-03-09
Keywords: Biotic stress; Chemiluminescence; Hydrogen peroxide; Luminol; Oxidative burst; Plant development; Reactive oxygen species (ROS); Stress response; Superoxide anion

Quinones shuffling the CARDs - Körner, Max; Slaby, Peter; Albert, Markus (Nature Plants, 2020)
CRIS-Team Scopus Importer:2020-09-11

Regulation of cell behaviour by plant receptor kinases: Pattern recognition receptors as prototypical models - Albert, Markus; Jehle, Anna K.; Lipschis, Martin; Mueller, Katharina; Zeng, Yi; Felix, Georg (European Journal of Cell Biology, 2010)
In this review we focus on pattern recognition receptors in plants that detect extracellular signals indicative for pathogen attack and injury. We start out with a discussion on FLS2, which binds and responds to bacterial flagellin, and then concentrate on ligand-receptor interactions as initial steps in the molecular receptor activation process. Comparison with other receptor kinases, whether involved in plant immunity or regulation of other cellular programs, might indicate common principles of receptor activation. © 2009 Elsevier GmbH.
CRIS-Team Scopus Importer:2020-03-09
Keywords: Address-message concept; Microbe-associated molecular patterns; Pattern recognition receptors; Plant; Receptor-like kinases

Significance of Cuscutain, a cysteine protease from Cuscuta reflexa, in host-parasite interactions - Bleischwitz, Marc; Albert, Markus; Fuchsbauer, Hans-Lothar; Kaldenhoff, Ralf (BMC Plant Biology, 2010)
Background: Plant infestation with parasitic weeds like Cuscuta reflexa induces morphological as well as biochemical changes in the host and the parasite. These modifications could be caused by a change in protein or gene activity. Using a comparative macroarray approach Cuscuta genes specifically upregulated at the host attachment site were identified.Results: One of the infestation specific Cuscuta genes encodes a cysteine protease. The protein and its intrinsic inhibitory peptide were heterologously expressed, purified and biochemically characterized. The haustoria specific enzyme was named cuscutain in accordance with similar proteins from other plants, e.g. papaya. The role of cuscutain and its inhibitor during the host parasite interaction was studied by external application of an inhibitor suspension, which induced a significant reduction of successful infection events.Conclusions: The study provides new information about molecular events during the parasitic plant - host interaction. Inhibition of cuscutain cysteine proteinase could provide means for antagonizing parasitic plants. © 2010 Bleischwitz et al; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2020-03-09

The dynamics of root cap sloughing in Arabidopsis is regulated by peptide signalling - Shi, Chun-Lin; Von Wangenheim, Daniel; Herrmann, Ullrich; Wildhagen, Mari; Kulik, Ivan; Kopf, Andreas; Ishida, Takashi; Olsson, Vilde; Anker, Mari Kristine; Albert, Markus; Butenko, Melinka A.; Felix, Georg; et al. (Nature Plants, 2018)
The root cap protects the stem cell niche of angiosperm roots from damage. In Arabidopsis, lateral root cap (LRC) cells covering the meristematic zone are regularly lost through programmed cell death, while the outermost layer of the root cap covering the tip is repeatedly sloughed. Efficient coordination with stem cells producing new layers is needed to maintain a constant size of the cap. We present a signalling pair, the peptide IDA-LIKE1 (IDL1) and its receptor HAESA-LIKE2 (HSL2), mediating such communication. Live imaging over several days characterized this process from initial fractures in LRC cell files to full separation of a layer. Enhanced expression of IDL1 in the separating root cap layers resulted in increased frequency of sloughing, balanced with generation of new layers in a HSL2-dependent manner. Transcriptome analyses linked IDL1-HSL2 signalling to the transcription factors BEARSKIN1/2 and genes associated with programmed cell death. Mutations in either IDL1 or HSL2 slowed down cell division, maturation and separation. Thus, IDL1-HSL2 signalling potentiates dynamic regulation of the homeostatic balance between stem cell division and sloughing activity.
CRIS-Team Scopus Importer:2020-03-09

The pattern-recognition receptor CORE of Solanaceae detects bacterial cold-shock protein - Wang, Lei; Albert, Markus; Einig, Elias; Fuerst, Ursula; Krust, Damaris; Felix, Georg (Nature Plants, 2016)
Plants and animals recognize microbial invaders by detecting microbe-associated molecular patterns (MAMPs) by cell surface receptors. Many plant species of the Solanaceae family detect the highly conserved nucleic acid binding motif RNP-1 of bacterial cold-shock proteins (CSPs), represented by the peptide csp22, as a MAMP. Here, we exploited the natural variation in csp22 perception observed between cultivated tomato (Solanum lycopersicum) and Solanum pennellii to map and identify the leucine-rich repeat (LRR) receptor kinase CORE (cold shock protein receptor) of tomato as the specific, high-affinity receptor site for csp22. Corroborating its function as a genuine receptor, heterologous expression of CORE in Arabidopsis thaliana conferred full sensitivity to csp22 and, importantly, it also rendered these plants more resistant to infection by the bacterial pathogen Pseudomonas syringae pv. tomato DC3000. Our study also confirms the biotechnological potential of enhancing plant immunity by interspecies transfer of highly effective pattern-recognition receptors such as CORE to different plant families.
CRIS-Team Scopus Importer:2020-03-09

The plant vampire diaries: a historic perspective on Cuscuta research - Hartenstein, Maleen; Albert, Markus; Krause, Kirsten (Journal of Experimental Botany, 2023)
The angiosperm genus Cuscuta lives as an almost achlorophyllous root- and leafless holoparasite and has therefore occupied scientists for more than a century. The 'evolution' of Cuscuta research started with early studies that established the phylogenetic framework for this unusual genus. It continued to produce groundbreaking cytological, morphological, and physiological insight throughout the second half of the 20th century and culminated in the last two decades in exciting discoveries regarding the molecular basis of Cuscuta parasitism that were facilitated by the modern 'omics' tools and traceable fluorescent marker technologies of the 21st century. This review will show how present activities are inspired by those past breakthroughs. It will describe significant milestones and recurring themes of Cuscuta research and connect these to the remaining as well as newly evolving questions and future directions in this research field that is expected to sustain its strong growth in the future.
CRIS-Team WoS Importer:2023-04-07

The receptor-like protein ReMAX of Arabidopsis detects the microbe-associated molecular pattern eMax from Xanthomonas - Jehle, Anna Kristina; Lipschis, Martin; Albert, Markus; Fallahzadeh-Mamaghani, Vahid; Fuerst, Ursula; Mueller, Katharina; Felix, Georg (The Plant Cell, 2013)
As part of their immune system, plants have pattern recognition receptors (PRRs) that can detect a broad range of microbeassociated molecular patterns (MAMPs). Here, we identified a PRR of Arabidopsis thaliana with specificity for the bacterial MAMP eMax from xanthomonads. Response to eMax seems to be restricted to the Brassicaceae family and also varied among different accessions of Arabidopsis. In crosses between sensitive accessions and the insensitive accession Shakhdara, eMax perception mapped to RECEPTOR-LIKE PROTEIN1 (RLP1). Functional complementation of rlp1 mutants required gene constructs that code for a longer version of RLP1 that we termed ReMAX (for receptor of eMax). ReMAX/RLP1 is a typical RLP with structural similarity to the tomato (Solanum lycopersicum) RLP Eix2, which detects fungal xylanase as a MAMP. Attempts to demonstrate receptor function by interfamily transfer of ReMAX to Nicotiana benthamiana were successful after using hybrid receptors with the C-terminal part of ReMAX replaced by that of Eix2. These results show that ReMAX determines specificity for eMax. They also demonstrate hybrid receptor technology as a promising tool to overcome problems that impede interfamily transfer of PRRs to enhance pathogen detection in crop plants. © 2013 American Society of Plant Biologists. All rights reserved.
CRIS-Team Scopus Importer:2020-03-09

The rice immune receptor XA21 recognizes a tyrosine-sulfated protein from a Gram-negative bacterium - Pruitt, Rory N.; Schwessinger, Benjamin; Joe, Anna; Thomas, Nicholas; Liu, Furong; Albert, Markus; Robinson, Michelle R.; Chan, Leanne Jade G.; Luu, Dee Dee; Chen, Huamin; Bahar, Ofir; Daudi, Arsalan; et al. (Science Advances, 2015)
Surveillance of the extracellular environment by immune receptors is of central importance to eukaryotic survival. The rice receptor kinase XA21, which confers robust resistance to most strains of the Gram-negative bacterium Xanthomonas oryzae pv. oryzae (Xoo), is representative of a large class of cell surface immune receptors in plants and animals. We report the identification of a previously undescribed Xoo protein, called RaxX, which is required for activation of XA21-mediated immunity. Xoo strains that lack RaxX, or carry mutations in the single RaxX tyrosine residue (Y41), are able to evade XA21-mediated immunity. Y41 of RaxX is sulfated by the prokaryotic tyrosine sulfotransferase RaxST. Sulfated, but not nonsulfated, RaxX triggers hallmarks of the plant immune response in an XA21-dependent manner. A sulfated, 21–amino acid synthetic RaxX peptide (RaxX21-sY) is sufficient for this activity. Xoo field isolates that overcome XA21-mediated immunity encode an alternate raxX allele, suggesting that co-evolutionary interactions between host and pathogen contribute to RaxX diversification. RaxX is highly conserved in many plant pathogenic Xanthomonas species. The new insights gained from the discovery and characterization of the sulfated protein, RaxX, can be applied to the development of resistant crop varieties and therapeutic reagents that have the potential to block microbial infection of both plants and animals.
CRIS-Team Scopus Importer:2020-03-09

The systemin receptor SYR1 enhances resistance of tomato against herbivorous insects - Wang, Lei; Einig, Elias; Almeida-Trapp, Marilia; Albert, Markus; Fliegmann, Judith; Mithoefer, Axel; Kalbacher, Hubert; Felix, Georg (Nature Plants, 2018)
The discovery in tomato of systemin, the first plant peptide hormone 1,2, was a fundamental change for the concept of plant hormones. Numerous other peptides have since been shown to play regulatory roles in many aspects of the plant life, including growth, development, fertilization and interactions with symbiotic organisms 3-6 . Systemin, an 18 amino acid peptide derived from a larger precursor protein 7, was proposed to act as the spreading signal that triggers systemic defence responses observed in plants after wounding or attack by herbivores 1,7,8 . Further work culminated in the identification of a leucine-rich repeat receptor kinase (LRR-RK) as the systemin receptor 160 (SR160) 9,10 . SR160 is a tomato homologue of Brassinosteroid Insensitive 1 (BRI1), which mediates the regulation of growth and development in response to the steroid hormone brassinolide 11-13 . However, a role of SR160/BRI1 as systemin receptor could not be corroborated by others 14-16 . Here, we demonstrate that perception of systemin depends on a pair of distinct LRR-RKs termed SYR1 and SYR2. SYR1 acts as a genuine systemin receptor that binds systemin with high affinity and specificity. Further, we show that presence of SYR1, although not decisive for local and systemic wound responses, is important for defence against insect herbivory.
CRIS-Team Scopus Importer:2020-03-09

The tomato receptor CuRe1 senses a cell wall protein to identify Cuscuta as a pathogen - Hegenauer, Volker; Slaby, Peter; Körner, Max; Bruckmueller, Julien-Alexander; Burggraf, Ronja; Albert, Isabell; Kaiser, Bettina; Loeffelhardt, Birgit; Droste-Borel, Irina; Sklenar, Jan; Menke, Frank L. H.; Macek, Boris; et al. (Nature Communications, 2020)
Parasitic plants of the genus Cuscuta penetrate shoots of host plants with haustoria and build a connection to the host vasculature to exhaust water, solutes and carbohydrates. Such infections usually stay unrecognized by the host and lead to harmful host plant damage. Here, we show a molecular mechanism of how plants can sense parasitic Cuscuta. We isolated an 11 kDa protein of the parasite cell wall and identified it as a glycine-rich protein (GRP). This GRP, as well as its minimal peptide epitope Crip21, serve as a pathogen-associated molecular pattern and specifically bind and activate a membrane-bound immune receptor of tomato, the Cuscuta Receptor 1 (CuRe1), leading to defense responses in resistant hosts. These findings provide the initial steps to understand the resistance mechanisms against parasitic plants and further offer great potential for protecting crops by engineering resistance against parasitic plants.
Created from Fastlane, Scopus look-up

Tools and strategies to match peptide-ligand receptor pairs - Butenko, Melinka A.; Wildhagen, Mari; Albert, Markus; Jehle, Anna; Kalbacher, Hubert; Aalen, Reidunn B.; Felix, Georg (The Plant Cell, 2014)
Peptide signals have emerged as an important class of regulators in cell-to-cell communication in plants. Several families of small, secreted proteins with a conserved C-terminal Pro-rich motif have been identified as functional peptide signals in Arabidopsis thaliana. These proteins are presumed to be trimmed proteolytically and undergo posttranslational modifications, such as hydroxylation of Pro residues and glycosylation, to form mature, bioactive signals. Identification and matching of such ligands with their respective receptors remains a major challenge since the genes encoding them often show redundancy and low expression restricted to a few cells or particular developmental stages. To overcome these difficulties, we propose the use of ectopic expression of receptor genes in suitable plant cells like Nicotiana benthamiana for testing ligand candidates in receptor output assays and in binding studies. As an example, we used the IDA peptide HAE/HSL2 receptor signaling system known to regulate floral organ abscission. We demonstrate that the oxidative burst response can be employed as readout for receptor activation by synthetic peptides and that a new, highly sensitive, nonradioactive labeling approach can be used to reveal a direct correlation between peptide activity and receptor affinity. We suggest that these approaches will be of broad value for the field of ligand-receptor studies in plants. © 2014 American Society of Plant Biologists. All rights reserved.
CRIS-Team Scopus Importer:2020-03-09